A new sauropod (Macronaria, Titanosauria) from the Adamantina Formation, Bauru Group, Upper Cretaceous of Brazil and the phylogenetic relationships of Aeolosaurini - Santucci, Rodrigo M.; de Arruda-Campos, Antonio C. (Zootaxa, 2011)
Remains of a new titanosaur, Aeolosaurus maximus sp. nov., from the Adamantina Formation (Upper Cretaceous), Bauru Group, São Paulo State of Brazil are described. The new species is represented by a single partially articulated skeleton and is characterized by having a well-developed posterior protuberance below the articular area on the anterior and middle haemal arches and a lateral bulge on the distal portion of the articular process of the mid-posterior haemal arches. It shares with other Aeolosaurus species the presence of prezygapophyses curved downward on anterior caudal vertebrae and haemal arches with double articular facets set in a concave posterodorsal surface. These two characteristics are interpreted here as synapomorphies for the genus Aeolosaurus. The new diagnosis for the genus Aeolosaurus does not support the inclusion of Gondwanatitan within Aeolosaurus as previously proposed by some authors. The phylogenetic analysis recovered the two Aeolosaurus from Argentina as sister groups with A. maximus and Gondwanatitan as progressively more basal taxa (Gondwanatitan (A. maximus (A. rionegrinus, A. colhuehuapensis))). Additionally, according to the results of the phylogenetic analysis performed in this work, the taxa Panamericansaurus, Rinconsaurus, and Maxakalisaurus are also nested within Aeolosaurini, being more basal than Aeolosaurus and Gondwanatitan. On the basis of the stratigraph-ical range of the Aeolosaurus occurrences in Argentina and the age proposals based on microfossils for the Bauru Group, it is assumed a Campanian–Maastrichtian age for the top of the Adamantina Formation for the Monte Alto region in São Paulo State and the bottom of the Marília Formation in Peirópolis, Minas Gerais State—the places where Aeolosaurus remains have been reported in Brazil.